XANTHOGRANULOMATOUS PYELONEPHRITIS - Mufti, Tariq (Journal of Ayub Medical College Abbottabad, 1989)
Abstract: A case of xanthogranulomatous pyelonephritis is presented. It is an uncommon but well recognised entity of chronic bacterial pyelonephritis which may easily be mistaken for renal cell carcinoma, renal carbuncle or tuberculosis.